Strategi Nabi Yusuf As Menghadapi Krisis Ekonomi Mesir Dalam Tujuh Tahun - Muslimin (Dinar : Jurnal Prodi Ekonomi Syariah, 2020)
The barn that the Prophet Yusup once built was a place of grain storage as a food reserve in the time of paceklik, playing a role in overcoming people's food insecurity. The food barn of joseph's line of thought, and became part of the system in which the people's food reserves were. The existence of food barns is customized and in the design of the state of musin as well as the egyptian weather. The application of the barn revolution that introverted the technology of the era, and the modernization of agriculture was judged in accordance with the traditional barns of the kingdom of Egypt and its climate, played a role in stabilizing food supply and prices, in each region to store wheat, no globalization led to the awakening of various foods, including processed food up to seven years, consistent coaching activities and tend to orientation projects led to the construction of effectively carried out. The existence of food barns at that time was needed. generally located in areas where large agricultural land has traditionally developed food barns in food-prone areas with accessibility constraints. Food barns play a role in addressing people's food insecurity in chronic food-prone areas, able to overcome transient food insecurity due to the conditions facing the paceklik. To overcome transient food insecurity, it is necessary to provide food reserves by the government that allows the mobility of food reserves between regions to be sufficient and smooth. With this brilliant idea the role of barns is needed to maintain institutional food reserves in the era of the food crisis. The institutional development of the government's food reserves can cooperate with private institutions or cooperate with KUWIL in the procurement of regional food reserves. The handling of food insecurity is also very closely related to the alleviation of hunger. Therefore, the prevention of food insecurity is not only related to the agricultural aspect and the provision of food but appropriate for the place to store food itself is really able to maintain food stuff for seven years, currently the place is popular name called BULOG.